Objective Comparison of the Quality and Reliability of Auditory Brainstem Response Features Elicited by Click and Speech Sounds. Issue 3 (May 2019) - Novis, Kimberley; Bell, Steven
Abstract : Objectives: Auditory brainstem responses (ABRs) are commonly generated using simple, transient stimuli (e.g., clicks or tone bursts). While resulting waveforms are undeniably valuable clinical tools, they are unlikely to be representative of responses to more complex, behaviorally relevant sounds such as speech. There has been interest in the use of more complex stimuli to elicit the ABR, with considerable work focusing on the use of synthetically generated consonant–vowel (CV) stimuli. Such responses may be sensitive to a range of clinical conditions and to the effects of auditory training. Several ABR features have been documented in response to CV stimuli; however, an important issue is how robust such features are. In the current research, we use time- and frequency-domain objective measures of quality to compare the reliability of Wave V of the click-evoked ABR to that of waves elicited by the CV stimulus /da/. Design: Stimuli were presented to 16 subjects at 70 dB nHL in quiet for 6000 epochs. The presence and quality of response features across subjects were examined using F sp and a Bootstrap analysis method, which was used to assign p values to ABR features for individual recordings in both time and frequency domains. Results: All consistent peaks identified within the /da/-evoked response had significantly lower amplitude than Wave V of the ABR. The morphology of speech-evoked waveforms varied across subjects. Mean F sp values for several waves of the speech-evoked ABR were below 3, suggesting low quality. The most robust response to the /da/ stimulus appeared to be an offset response. Only click-evoked Wave V showed 100% wave presence. Responses to the /da/ stimulus showed lower wave detectability. Frequency-domain analysis showed stronger and more consistent activity evoked by clicks than by /da/. Only the click ABR had consistent time–frequency domain features across all subjects. Conclusions: Based on the objective analysis used within this investigation, it appears that the quality of speech-evoked ABR is generally less than that of click-evoked responses, although the quality of responses may be improved by increasing the number of epochs or the stimulation level. This may have implications for the clinical use of speech-evoked ABR.